Overexpression of CD73 is associated with recurrence and poor prognosis of gingivobuccal oral cancer as revealed by transcriptome and deep immune profiling of paired tumor and margin tissues - Ankita Chatterjee; Amrita Chaudhary; Arnab Ghosh; Pattatheyil Arun; Geetashree Mukherjee; Indu Arun; Arindam Maitra; Nidhan Biswas; Partha P. Majumder (Cancer Medicine, 2023)
Abstract Background For various cancers, differences in response to treatment and subsequent survival period have been reported to be associated with variation in immune contextures. Aim We sought to identify whether such association exists in respect of gingivobuccal oral cancer. Materials and methods We performed deep immune profiling of tumor and margin tissues collected from 46 treatment naïve, Human Papillomavirus (HPV) negative, patients. Each patient was followed for 24 months and prognosis (recurrence/death) noted. Key findings were validated by comparing with TCGA‐HNSC cohort data. Results About 28% of patients showed poor post‐treatment prognosis. These patients exhibited a high probability of recurrence even within 1 year and death within 2 years. There was restricted immune cell infiltration in tumor, but not in margin, among these patients. Reduced expression of eight immune‐related genes (IRGs) (NT5E, THRA, RBP1, TLR4, ITGA6, BMPR1B, ITGAV, SSTR1) in tumor strongly predicted better quality of prognosis, both in our patient cohort and in TCGA‐HNSC cohort. Tumors of patients with better prognosis were associated with (a) lower CD73+ cells with concomitant lower expression level of NT5E/CD73, (b) higher proportions of CD4+ and CD8+ T cells, B cells, NK cells, M1 macrophages, (c) higher %Granzyme+ cells, (d) higher TCR and BCR repertoire diversities. CD73 expression in tumor was associated with low CD8+ and CD4+ T cells, low immune repertoire diversity, and advanced cancer stage. Discussion and conclusion High infiltration of anti‐tumor immune cells in both tumors and margins results in good prognosis, while in patients with minimal infiltration in tumors in spite of high infiltration in margins results in poor prognosis. Targeted CD73 immune‐checkpoint inhibition may improve clinical outcome.